The Gospel of John : more light from Philo, Paul and archaeology : the Scriptures, Tradition, Exposition, Settings, Meaning - Borgen, Peder. (Novum Testamentum, Supplements, 2014)
To Paul the traditions from and about Jesus had authority similar to that of the Scriptures: a logion or story served as text for paraphrastic expositions. Such expositions are also seen in John's Gospel. - It is insufficient to discuss 'John and the Synoptics'. A better scope is 'John within early gospel traditions'.- Paul and Philo maintain a cosmic understanding of Jesus and the Jewish people, respectively. Correspondingly, Jesus is seen in cosmological perspective in John's Prologue. Philo illuminates the role of God's logos relative to creation and revelation. - Archaeology testifies to the reliability of John's topographical references. Both John and Philo can combine theological and ideological elaborations with specific geographical references, historical events and religious feasts. The study has brought in material and perspectives which strengthen the view that the Gospel of John was independent of the other three written gospels.